Complete Sequence of a Novel IncR-F33:A–:B– Plasmid, pKP1034, Harboring fosA3, bla(KPC-2), bla(CTX-M-65), bla(SHV-12), and rmtB from an Epidemic Klebsiella pneumoniae Sequence Type 11 Strain in China - Xiang, Dai-Rong (Antimicrob Agents Chemother, 2016)
A high fosfomycin resistance rate was observed in Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-KP) in our previous study, but little is known about its mechanisms. In this study, we explored the prevalence of plasmid-mediated fosfomycin resistance determinants among fosfomycin-resistant KPC-KP strains from a Chinese university hospital and determined the complete sequence of a novel fosA3-carrying plasmid isolated from an epidemic K. pneumoniae sequence type (ST) 11 strain. A total of 97 KPC-KP strains were studied, of which 57 (58.8%) were resistant to fosfomycin, including 44 (45.4%) harboring fosA3 and 1 harboring fosA. All fosA3-positive strains belonged to the dominant ST11-pulse type (PT) A clone according to multilocus sequence typing and pulsed-field gel electrophoresis, suggesting clonal dissemination. The fosA-positive isolate belonged to ST11-PTE. The fosA3-carrying plasmid pKP1034 is 136,848 bp in length and is not self-transmissible. It is a multireplicon plasmid belonging to IncR-F33:A−: B−. Besides fosA3, a variety of other resistance determinants, including bla(KPC-2), rmtB, bla(CTX-M-65), and bla(SHV-12), are identified in pKP1034, which would allow for coselection of fosA3 by most β-lactams and/or aminoglycosides and facilitate its dissemination despite limited use of fosfomycin in China. Detailed comparisons with related plasmids revealed that pKP1034 is highly mosaic and might have evolved from alarming recombination of the bla(KPC-2)-carrying plasmid pKPC-LK30 from Taiwan and the epidemic fosA3-carrying plasmid pHN7A8 from mainland China.